Altered Resting‐State Intranetwork and Internetwork Functional Connectivity in Patients With Chronic Unilateral Vestibulopathy. Issue 1 (18th December 2021) - Si, Lihong; Cui, Bin; Li, Zheyuan; Li, Xiang; Li, Kangzhi; Ling, Xia; Shen, Bo; Yang, Xu
Abstract : Background: Chronic unilateral vestibulopathy (CUVP) is often accompanied by dizziness and postural instability, which restrict patients' daily activities. It is important to understand central compensation mechanisms underlying these symptoms in patients with CUVP by evaluating their brain functional status. Purpose: To analyze the changes in resting‐state intranetwork and internetwork functional connectivity (FC) and explore the state of central vestibular compensation in patients with CUVP. Study type: Retrospective. Population: Eighteen patients with right‐sided CUVP and 18 age‐ and sex‐matched healthy controls. Field strength/sequence: A 3.0 T, three‐dimensional magnetization‐prepared rapid gradient‐echo (MP‐RAGE) and resting‐state echo‐planar imaging (EPI) functional MRI sequences. Assessment: FC alterations were explored using independent component analysis (ICA). Twelve independent components were identified via ICA. Dizziness Handicap Inventory (DHI) score for all patients was determined. Statistical tests: Two‐sample t test, family‐wise error (FWE) correction, Pearson correlation coefficient ( r ). A P value <0.05 was considered statistically significant. Results: Compared with healthy controls, patients with CUVP showed significantly decreased FC in the right middle occipital gyrus within the lateral visual network, and significantly increased FC in the right supplementary motor area within the sensorimotor network. The FC was decreased between the medial visual and auditory networks, the right frontoparietal and posterior default networks, as well as the sensorimotor and auditory networks. There was a significant negative correlation between the FC changes in the visual, auditory networks and the DHI score in patients with CUVP ( r = −0.583). Data conclusion: Compared to healthy controls, the FC was significantly decreased in the right visual cortex and significantly enhanced in the right sensorimotor network in patients with CUVP. Patients with CUVP showed decreased FC between multiple whole‐brain networks, suggesting that abnormal integration of multisensory information may be involved in the occurrence of chronic dizziness and instability in patients with CUVP. Level of evidence: 4 Technical Efficacy: Stage 2.